2023
DOI: 10.1017/jns.2023.37
|View full text |Cite
|
Sign up to set email alerts
|

REDD1 deletion and treadmill running increase liver hepcidin and gluconeogenic enzymes in male mice

Abstract: The iron-regulatory hormone hepcidin is transcriptionally up-regulated by gluconeogenic signals. Recent evidence suggeststhat increases in circulating hepcidin may decrease dietary iron absorption following prolonged exercise, however evidence is limited on whether gluconeogenic signals contribute to post-exercise increases in hepcidin. Mice with genetic knockout of regulated in development and DNA response-1 (REDD1) display greater glycogen depletion following exercise, possibly indicating greater gluconeogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In sports, hepcidin can increase due to the activation of the CREBH pathway [29]. A recent study conducted on mice demonstrated how the depletion of glucose reserves during physical activity stimulates the release of hepcidin, through gluconeogenetic signals [76]. The increase in hepcidin levels after sporting activity can reduce the availability of iron introduced by diet or supplements, and promote both iron deficiency and anemia.…”
Section: Anemic States Characterized By the Increase In Hepcidin Releasementioning
confidence: 99%
“…In sports, hepcidin can increase due to the activation of the CREBH pathway [29]. A recent study conducted on mice demonstrated how the depletion of glucose reserves during physical activity stimulates the release of hepcidin, through gluconeogenetic signals [76]. The increase in hepcidin levels after sporting activity can reduce the availability of iron introduced by diet or supplements, and promote both iron deficiency and anemia.…”
Section: Anemic States Characterized By the Increase In Hepcidin Releasementioning
confidence: 99%